2007
DOI: 10.1002/ijc.22529
|View full text |Cite
|
Sign up to set email alerts
|

Breast conservation: Current results and future perspectives at the European Institute of Oncology

Abstract: In the recent 10 years breast cancer treatments' scenario is radically changed. Extraordinary new surgical approaches give more and more conservative solutions both for the breast and especially for the axilla avoiding dissection in more than 80% of early cases. Instrumental early diagnosis and clinical prediction are now able to identify very initial cases often in premalignant stage. Technology arrived in the operating theatre for the intraoperative radiotherapy treatments giving to the patients the better q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 48 publications
0
8
1
3
Order By: Relevance
“…13 Many other factors can influence aesthetic results after lumpectomy: age, BMI, size and location of the tumor, breast size, as well as the adjuvant treatment applied. Our findings showed an association of increased age with unsatisfactory results in the lumpectomy group, especially 28 Approximately 35 % of breast tumors are located in the lower (inner or outer) quadrants, 29 and in lumpectomy this localization is a risk one (the same for inner and central quadrants), because loss of tissue there can distort and lower the nipple and areola complex. Another relevant data in our series was in relation to the breast size, because larger breasts were related with worse aesthetic outcomes in the lumpectomy group.…”
Section: Discussionmentioning
confidence: 84%
“…13 Many other factors can influence aesthetic results after lumpectomy: age, BMI, size and location of the tumor, breast size, as well as the adjuvant treatment applied. Our findings showed an association of increased age with unsatisfactory results in the lumpectomy group, especially 28 Approximately 35 % of breast tumors are located in the lower (inner or outer) quadrants, 29 and in lumpectomy this localization is a risk one (the same for inner and central quadrants), because loss of tissue there can distort and lower the nipple and areola complex. Another relevant data in our series was in relation to the breast size, because larger breasts were related with worse aesthetic outcomes in the lumpectomy group.…”
Section: Discussionmentioning
confidence: 84%
“…As a result, sentinel lymph node biopsy (SLNB), a minimally invasive technique, was developed to avoid lymph node dissection in patients who have a low probability of axillary metastasis (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). The sentinel node is the first lymph node which receives lymph from the anatomic site of the primary breast tumour.…”
Section: Sentinel Node Biopsymentioning
confidence: 99%
“…Following a lumpectomy, postoperative radiation treatment is always applied (Fisger et al 2002). Since Veronesi began with breast conserving surgery in patients with diagnosed breast cancer, numerous studies have confirmed the equal oncological value of this type of surgery compared with a classic mastectomy (Veronesi & Zurrida 2007). Although this type of surgery is minimally destructive, our experience as well as experience of other authors has shown that the cosmetic result is not always satisfactory (Stanton et al 2001, Medina -Franco et al 2013) Due to this, many authors have researched the influence of the cosmetic result after breast conserving therapy and observed important factors such as postoperative complications, tumor location and volume of excised tissue (tumor removal) versus breast volume (Cardoso et al 2007).…”
Section: Introductionmentioning
confidence: 99%